Atividade da redutase de nitrato em mudas de pupunheira (Bactris gasipaes) - Oliveira, Maria Aparecida José De; Bovi, Marilene Leão Alves; Machado, Eduardo Caruso; Rodrigues, João Domingos [UNESP] (Universidade Federal de Santa Maria, 2005)
The nitrate reductase enzyme (EC 1.6.6.1) is the main responsible enzyme for the assimilation of nitrogen by plants and its activity is strongly affected by the soil water availability. This feature allows the use of this enzyme to evaluate plants in different environmental conditions. The objective of this study was to standardize the methodology to evaluate in vivo the nitrate reductase activity in leaves and roots of nine months and one year old peach palms (Bactris gasipaes). The plants were cultivated in a nursery and the essays were conducted according to the classical method of in vivo analyses. The experimental design was entirely randomized with six repetitions. The results showed that maximum nitrate reductase activity for leaves was obtained with an incubation time of 60 minutes, pH 7, temperatures from 35 to 37°C and, nitrate concentrations between 28 and 30mmol L-1. The nitrate reductase enzyme activity was higher in nine months than in one year old palms. The peach palm leaves showed higher enzyme activity than roots. The nitrate reductase activity varied during the day, with maximum activity at 10:00 hs, indicating an influenceby light and leaf water potential.

A enzima redutase de nitrato (EC 1.6.6.1) é a principal enzima responsável pela assimilação de nitrogênio pelas plantas e tem a atividade fortemente afetada pela disponibilidade de água no solo, por isso é usada como variável na avaliação das plantas em diferentes condições ambientais. Assim, este estudo teve como objetivo a padronização de metodologia para avaliação in vivo da atividade da redutase de nitrato em folhas e raízes de pupunheira com nove meses e um ano. As mudas foram cultivadas em casa de vegetação, e os ensaios realizados de acordo com método clássico de análise in vivo. O delineamento experimental foi inteiramente casualizado, com seis repetições. A atividade máxima da enzima em folhas foi obtida com tempo de incubação ao redor de 60 minutos, pH do meio de reação em torno de 7, temperatura de 35 a 37°C e concentração de nitrato entre 28 a 30mmolL-1. A atividade desta enzima foi maior em plantas com nove meses de idade. As folhas mostraram maior atividade da enzima quando comparadas com as raízes. A atividade da enzima redutase de nitrato variou ao longo do dia, com máxima obtida às 10:00 horas, mostrando a influência do período luminoso e do estado hídrico da planta.
Nitrate reductase activity in peach palm (Bactris gasipaes) seedlings
Keywords: Bactris gasipaes; nitrate reductase enzyme; light; temperature; nitrate concentration; Bactris gasipaes; enzima redutase de nitrato; luz; temperatura; concentração de nitrato